Repurposing of antibiotics for clinical management of COVID-19: a narrative review - Abdourahamane Yacouba; Ahmed Olowo-okere; Ismaeel Yunusa (BMC, 2021)
Abstract Background Drug repurposing otherwise known as drug repositioning or drug re-profiling is a time-tested approach in drug discovery through which new medical uses are being established for already known drugs. Antibiotics are among the pharmacological agents being investigated for potential anti-SARS-COV-2 activities. The antibiotics are used either to resolve bacterial infections co-existing with COVID-19 infections or exploitation of their potential antiviral activities. Herein, we aimed to review the various antibiotics that have been repositioned for the management of COVID-19. Methods This literature review was conducted from a methodical search on PubMed and Web of Science regarding antibiotics used in patients with COVID-19 up to July 5, 2020. Results Macrolide and specifically azithromycin is the most common antibiotic used in the clinical management of COVID-19. The other antibiotics used in COVID-19 includes teicoplanin, clarithromycin, doxycycline, tetracyclines, levofloxacin, moxifloxacin, ciprofloxacin, and cefuroxime. In patients with COVID-19, antibiotics are used for their immune-modulating, anti-inflammatory, and antiviral properties. The precise antiviral mechanism of most of these antibiotics has not been determined. Moreover, the use of some of these antibiotics against SARS-CoV-2 infection remains highly controversial and not widely accepted. Conclusion The heavy use of antibiotics during the COVID-19 pandemic would likely worsen antibiotic resistance crisis. Consequently, antibiotic stewardship should be strengthened in order to prevent the impacts of COVID-19 on the antibiotic resistance crisis.